1995
DOI: 10.1523/jneurosci.15-11-07315.1995
|View full text |Cite
|
Sign up to set email alerts
|

Basal forebrain cholinergic lesions disrupt increments but not decrements in conditioned stimulus processing

Abstract: Magnocellular neurons in the basal forebrain provide the major cholinergic innervation of cortex. Recent research suggests that this cholinergic system plays an important role in the regulation of attentional processes. The present study examined the ability of rats with selective immunotoxic lesions of these neurons (made with 192 IgG-saporin) to modulate attention within an associative learning framework. Each rat was exposed to conditioned stimuli (CS) that were either consistent or inconsistent predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
200
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(225 citation statements)
references
References 38 publications
21
200
4
Order By: Relevance
“…Likewise, whereas in intact rats the surprising omission of anticipated events increases attention to stimuli that accompany that surprise, enhancing subsequent learning about those stimuli, rats with CeA lesions fail to show such enhancement (Holland and Gallagher, 1993). Other studies from our laboratory show that these surprise-induced enhancements of attention are mediated by circuitry that includes the CeA, cholinergic neurons in the basal forebrain nucleus basalis/substantia innominata, and the posterior parietal cortex (Chiba et al, 1995;Bucci et al, 1998;Han et al, 1999). Thus, it appears that the CeA can regulate various aspects of attentional information processing through its influence on different brain circuitry.…”
Section: Discussionmentioning
confidence: 72%
“…Likewise, whereas in intact rats the surprising omission of anticipated events increases attention to stimuli that accompany that surprise, enhancing subsequent learning about those stimuli, rats with CeA lesions fail to show such enhancement (Holland and Gallagher, 1993). Other studies from our laboratory show that these surprise-induced enhancements of attention are mediated by circuitry that includes the CeA, cholinergic neurons in the basal forebrain nucleus basalis/substantia innominata, and the posterior parietal cortex (Chiba et al, 1995;Bucci et al, 1998;Han et al, 1999). Thus, it appears that the CeA can regulate various aspects of attentional information processing through its influence on different brain circuitry.…”
Section: Discussionmentioning
confidence: 72%
“…Other research with these same tasks has indicated that another system, which includes the central nucleus of the amygdala (CN) and its projections to the nucleus basalis magnocellularis /substantia innominata (nBM /SI), controls incremental processing independent of decremental processing: lesions of CN or of cholinergic neurons in the nBM /SI spare decremental processing (e.g., latent inhibition) but eliminate incremental processing (like that produced by the shift in the serial conditioning procedure; Holland and Gallagher, 1993;Chiba et al, 1995). Within this system cholinergic projections from the nBM /SI to neocortex are hypothesized to modulate information processing in the cortex (Holland and Gallagher, 1993;Gallagher and Holland, 1994;Chiba et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Within this system cholinergic projections from the nBM /SI to neocortex are hypothesized to modulate information processing in the cortex (Holland and Gallagher, 1993;Gallagher and Holland, 1994;Chiba et al, 1995). By analogy, the role of the hippocampus in decremental processing may be like that of CN in incremental processing; that is, it may regulate processing in cortical targets of the MS/ VDB (e.g., cingulate cortex) (Amaral and Kurz, 1985;Gaykema et al, 1990) via its efferent projections to the septum (Swanson, 1977;Swanson and Cowan, 1977;Gaykema et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the mnemonic effects produced by certain cholinergic manipulations suggests a role in enhancing cortical information processing to facilitate acquisition of new material (Chiba et al, 1995;Bucci et al, 1998;Furey et al, 2000;McGaughy et al, 2005), a function for cortical ACh that would be consistent with its broader role in attention (Sarter et al, 2003). Conversely, results from studies with postacquisition manipulations have suggested that ACh may be directly involved in memory consolidation.…”
Section: Introductionmentioning
confidence: 99%